Effect of UV illumination on perylene-doped luminescent solar concentrators: A cautionary tale. (1st September 2019) - Vingerhoets, Lex A.F.; ter Schiphorst, Jeroen; Hagen, Wilfred R.; Debije, Michael G.
Highlights: Demonstrate the generation of additional absorption peak after UV illumination in nitrogen. Extra absorption changes LSC color and reduces performance significantly. Generated absorption peak disappears after prolonged exposure to air. Absorption peak consistent with an anionic radical at perylene core. Oxygen important in repair mechanism for perylene-based LSC devices. Abstract: The luminescent solar concentrator has the potential of widespread use as a generator of electricity from sunlight well-suited for use in the urban environment owing to its adaptability in shape and coloration. The device performance is heavily dependent on the ability to transport light long distances to the edges. A common organic luminophore used in the device is based on a perylene core. In this work, we describe an overlooked effect of UV illumination on the appearance and efficiency of these devices. An additional absorption peak appears upon polymerization under intense UV in nitrogen atmosphere which significantly reduces the edge emissions from the device. The additional absorbance peak disappears after exposure to air, indicating the presence of a radical anion being formed during the UV light exposure. This suggests newly-produced LSC devices should be allowed to stand a period of time under ambient conditions before their performance characteristics are determined, which could have implications in potential future commercialization of the technology.